An improved convolution Merkle tree-based blockchain electronic medical record secure storage scheme. (September 2021) - Zhu, Hegui; Guo, Yujia; Zhang, Libo
Abstract: Presently, more and more electronic medical records (EMR) are used to replace traditional recording methods. However, there has potential safety hazard in the transmission of EMR because of the personal privacy disclosure. So, how to store, transmit and share EMR effectively and securely has become a research hotspot. In this paper, we propose an improved Merkle tree based-blockchain EMR storage scheme. The hallmark of the proposed scheme is that we employ the convolutional layer structure to replace the original binary tree structure in the proposed convolution Merkle tree, which can improve the efficiency effectively. Experiments show that the number of stored nodes has decreased significantly with the same amount of input data, and the layers number of the improved convolution Merkle tree and hash calculated amount are all reduced dramatically. The security and efficiency analysis also illustrate that the proposed scheme can provide a reliable choice for the further development of data storage security in the future. Highlights: Propose a new convolution operation based-Merkle tree structure. It can significantly reduce the number of layers and data calculation amount. The improved Merkle tree structure ensures the convenience of data storage. It provides a reliable choice for the further development of data storage security.